Altman Z-Score is a Method of Analyzing Bankruptcy - Mohammad Ilham; Nor Norisanti; Faizal Mulia Z (Almana : Jurnal Manajemen dan Bisnis, 2022)
Altman Z-Score is one of three bankruptcy prediction methods. This study aims to determine whether this manufacturing company is experiencing bankruptcy. The bankruptcy prediction method used in this research is the Altman Z-Score method which is equipped with a cut-off point to determine the bankruptcy classification. Altman used five financial ratios that cater for companies to go public Working Capital to Total Assets (X1), Retained Earnings to Total Assets(X2), Earnings Before Interest and Taxes to Total Assets(X3), and Total Equity to Total Assets (X4). This research was conducted on manufacturing companies listed on the Indonesian Stock Exchange. The results of calculations based on the Altman Z-Score Modification method from the 2020 - 2021 quarter period show that PT. Krakatau Steel Tbk is in an unhealthy condition or bankrupt because the average Z-Score value is below 1 or Z<1 which means PT. Krakatau Steel is experiencing unhealthy finances. And the company's financial condition was not good or went bankrupt, resulting from the level of solvency that was not maximized, while other problems were caused by companies that could not manage capital properly.